1993
DOI: 10.1080/09553009314550271
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Chromatin Fragmentation in Chloroma Cell Apoptosis Is Highly Sensitive to UV and Begins at Non-B DNA Conformation

Abstract: UV irradiation induces programmed death, or apoptosis, in rat chloroleukaemia cells, a process characterized by typical cell morphology, fragmentation of chromatin into units of single and multiple nucleosomes, and transcriptional activation of LINE. Our study shows that this process is initiated by very low UV doses: exposure to one minimal erythema dose (MED, about 200 J/m2), at defined wavelengths ranging from 270 to 330 nm, is sufficient. By sequencing 100 randomly selected blunt-end chromatin fragments (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…For the LINE L1 material, approximately three quarters contained an apoptotic scission event within the repeat sequence itself. Thus, although the percentage of these repetitive elements within the sequence library matches that found in the entire genome, they are preferentially found at the site of apoptotic cleavage, confirming the results of others [Luokkamaki et al, 1993;Moore et al, 1993;Fan and Smith, 1995]. In the specific case of those cloned sites containing L1 elements, it was found that a proportion of them was clustered within a 300-bp region of the second ORF (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…For the LINE L1 material, approximately three quarters contained an apoptotic scission event within the repeat sequence itself. Thus, although the percentage of these repetitive elements within the sequence library matches that found in the entire genome, they are preferentially found at the site of apoptotic cleavage, confirming the results of others [Luokkamaki et al, 1993;Moore et al, 1993;Fan and Smith, 1995]. In the specific case of those cloned sites containing L1 elements, it was found that a proportion of them was clustered within a 300-bp region of the second ORF (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…These numbers are comparable to that reported in the literature for the genomic distribution of Alu and LINE elements [Kariya et al, 1987;Moran et al, 1999]. This would seem to be in contrast to other reports, in which apoptotic DNA fragments were reportedly enriched in repetitive DNA [Luokkamaki et al, 1993;Miore et al, 1993;Fan and Smith, 1995]. However, in this study we found that although the percentage of repetitive DNA within the entire cloned material was not elevated above normal levels, the location of the apoptotic cut site was biased toward both Alu and LINE locations.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Another approach to analyse the regional cleavage of chromosomal DNA during apoptosis was to clone and sequence the released oligonucleosomal DNA fragments. 27,30,31 Whereas the two former reports detected a relative accumulation of interspersed sequences (SINE and LINE) in the isolated fragments, Khodarev et al 27 observed a normal distribution of repetitive DNA within the entire cloned material. These authors observed, however, a preferential cleavage site in such repetitive sequences.…”
Section: Discussionmentioning
confidence: 89%